Development of low thermal mass cement-sand block utilizing peat soil and effective microorganism - Idris, I.H.M. (Elsevier Ltd, 2018)
The development of low thermal mass cement-sand block by incorporating peat soil and Effective Microorganism (EM) was studied systematically. In total, seven mixtures of cement-sand block targeted at a 28-days compressive strength of 7 MPa are designed. One control sample is made with a water/cement ratio (w/c) of 0.5, three mixes using 3, 6 and 10 peat soil replacing sand and three mixes using 10, 20 and 30 EM replacing water. Modified blocks with 6 of peat soil and 30 of EM are the most optimum blocks to be used in the construction of masonry as they successfully reduced the thermal conductivity of the blocks with the value of 1.275 W/mK and 1.792 W/mK respectively when being compared to the thermal conductivity of the control sample which is 2.400 W/mK. Besides, they are also able to achieve higher strength than the desired compressive strength which is 7 MPa. The compressive strength of the samples with 6 of peat soil is 16.48 MPa at 28-days while 30.39 MPa for samples with 30 of EM. On the other hand, the water absorption rate of samples with 6 of peat soil is 7.6 while 6.1 for samples with 30 EM and both are okay since their rate of water absorption is lower than 20. In conclusion, the addition of peat soil and EM in the cement-sand mix show promising performance as a low cost material to produce low thermal mass cement-sand block. Â© 2017 The Authors